Vaccine delivery: a matter of size, geometry, kinetics and molecular patterns. - Bachmann, M; Jennings, G (2010)
Researchers working on the development of vaccines face an inherent dilemma: to maximize immunogenicity without compromising safety and tolerability. Early vaccines often induced long-lived protective immune responses, but tolerability was a major problem. Newer vaccines have very few side effects but can be of limited immunogenicity. One way to tackle this problem is to design vaccines that have all the properties of pathogens with the exception of causing disease. Key features of pathogens that can be mimicked by vaccine delivery systems are their size, shape and surface molecule organization. In addition, pathogen-associated molecular patterns can be used to induce innate immune responses that promote adaptive immunity. In this Review, we discuss the approaches currently being used to optimize the delivery of antigens and enhance vaccine efficacy.